2017
DOI: 10.1177/1475240917694109
|View full text |Cite
|
Sign up to set email alerts
|

From language learner to language user in English-medium higher education: Language development brokers outside the language classroom

Abstract: This article explores, from within the social constructivist paradigm and drawing on data from twentyone semi-structured interviews with international postgraduate university students approaching the end of a one-year full-time taught Masters degree in the UK, the range of language development brokers that have had an impact on these students' trajectory from language learner to language user. Students from a range of first language backgrounds contributed insights about key people, outside formal language tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…For example, in Aizawa and Rose (2020) study, only students with previous English language learning and instruction experience reported advantageous and enabling effects of a university EMI experience. Similar was the case in Evans and Morrison (2011b, 2017, Kim et al (2014), Belhiah and Elhami (2015), Bolton et al (2017), Chu et al (2018), andHua (2020). Bolton et al (2017) reported the intermediary role of disciplinary background and level of study in positively informing these experiences.…”
Section: English Medium Instruction Experience: a Boonsupporting
confidence: 57%
See 1 more Smart Citation
“…For example, in Aizawa and Rose (2020) study, only students with previous English language learning and instruction experience reported advantageous and enabling effects of a university EMI experience. Similar was the case in Evans and Morrison (2011b, 2017, Kim et al (2014), Belhiah and Elhami (2015), Bolton et al (2017), Chu et al (2018), andHua (2020). Bolton et al (2017) reported the intermediary role of disciplinary background and level of study in positively informing these experiences.…”
Section: English Medium Instruction Experience: a Boonsupporting
confidence: 57%
“…Compared to the initial struggle, a perceived improvement in students' confidence in their writing and speaking skills is apparent. This change in the participants' proficiency level in their English language production skills can probably be explained as a transition of struggling learners (that the students were at the initial stage of their learning) into capable users (that the students are at the point of collecting data for this study) (Blaj-Ward, 2017).…”
Section: Academic Transition: Developmental Culminationmentioning
confidence: 99%